Effects of Maternal Factors and Postpartum Environment on Early Colonization of Intestinal Microbiota in Piglets - Li, Yongshi; Liu, Yadan; Ma, Yijia; Ge, Xusheng; Zhang, Xiaona; Cai, Chunbo; Yang, Yang; Lu, Chang; Liang, Guoming; Guo, Xiaohong; Cao, Guoqing; Li, Bugao; et al. (Frontiers in veterinary science, 2022)
Intestinal microbiota significantly influences the intake, storage, and utilization of body nutrients, as well as animal growth and development. The establishment of microbiota is affected by many factors, such as delivery and feeding modes, antibiotics, disease, and the surrounding environment. In this study, we selected Chinese indigenous Mashen and Jinfen White pigs as the study subjects. To explore the source and factors affecting the piglet intestinal microbiota, 16S rRNA gene sequencing was performed to analyze the microbial composition of the feces, saliva, vaginal secretions, and colostrum of parturient sows, feces and saliva of newborn piglets, and surrounding environment samples. The results showed that the microbiota of the saliva of sows and piglets is structurally similar to that of the environment and is dominated by the phylum Proteobacteria, including Acinetobacter, Actinomyces , and Pseudomonas . The core genus in the vaginal secretions and colostrum of sows was Pseudomonas . Among the fecal samples, the core bacterial genera in sows before and after delivery were Clostridium sensu_stricto_1 and Christensenellaceae_R-7_group , while in piglets at 1 d of age, Pseudomonas and Escherichia-Shigella were most abundant. These results indicate that microbiota in feces, colostrum, and vaginal secretions of sows more easily colonized piglet intestines through a symbiotic effect. The environmental and salivary microbiota could also affect the early colonization and succession of the intestinal microbiota of piglets to some extent. This study provides a theoretical basis for sow delivery protection and early nursing of piglets and background for the research and development of microbial agents to improve piglet intestinal health.